About the age and habitat of the Kirgilyakh mammoth (Dima), Western Beringia. (1st August 2016) - Lozhkin, A.V.; Anderson, P.M.
Abstract: The unearthing in 1977 of a complete frozen carcass of a young mammoth, known as the Kirgilyakh mammoth or Dima: 1) provided the first opportunity for detailed study of the anatomy of a mammoth calf; 2) provided a more detailed understanding of interstadial landscapes; and 3) suggested paleoclimatic variability occurred in Western Beringia during marine isotope stage (MIS) 3. Limited access to early Russian literature resulted in unfortunate misinformation in English-language publications. Since then, six other juvenile carcasses have been discovered in northern Siberia and additional Late Pleistocene paleobotanical records have increased understanding of MIS2 and MIS3 environments. Given the new data, it seems timely to re-examine information about the Kirgilyakh mammoth in the context of: 1) correcting mistakes about the age and environments of the site, including the manner of the mammoth's death; 2) comparing paleoenvironmental settings with that of other young mammoth carcasses; and 3) revisiting the concept of mammoth-steppe. This re-examination, which places the Kirgilyakh results in a broader spatial-temporal setting, reinforces the idea that climatic variability, including the Kirgilyakh cool interval, characterized MIS3. Unstable landscapes in mountains and lowlands were key factors in deaths of the Siberian mammoth calves. The prevalence of tundra in MIS2 model reconstructions and abundance of paleobotanical data indicating mesic tundra and forest during MIS3 suggest that classification of these intervals as mammoth-steppe is problematic. Highlights: The age, location, and manner of death of Dima are clarified. Kirgilyakh data document vegetation and climate variability during MIS3. The landscape was apparently as a factor in mammoths' deaths as other factors. The concept of mammoth-steppe needs rethinking in light of new paleobotanical data.